Study on the Influence of Polycarboxylate Superplasticizer Compound on the pump PHC. (September 2020) - Fang, Yunhui; Ke, Yuliang; Zhang, Xiaofang; Zhu, Shaohong; Qiu, Yuetao; Chen, Xiaobin; Lin, Tianxing; Guo, Yuanqiang; Ma, Xiuxing
Abstract: This aricle disclosed the effects of polycarboxylate superplasticizer (PCE), air entraining agent, defoamer, accelerator on the properties of prestressed high-strength concrete (PHC). The introduction of DAC and AMPS into the molecular structure of PCE is helpful to improve compressive strength of PHC. The air entraining agent can be used to improve the PHC workability. The Defoamers and accelerators are beneficial for increasing PHC compressive strength. The admixture compounding technology by using PCEs, air entraining agents, defoamers and accelerators can help to get excellent properties of PHC.